Nosocomial Infection in Al-Hilla City Hospital - Amean A. Yasir (Journal of Global Pharma Technology, 2018)
Some of the problems are reviewed. Methods suggested for dealing with them are probably not the ideals that should ultimately be attained but minimum standards to serve as immediate objectives for the search about Nosocomial infection. They concern indications for and methods of isolation control of infection from staff, environmental contamination, and a few technical procedures. A new type of dressing towel for wounds is described.Keywords: Nosocomial Infection, Control of infection, Healthcare-associated infection, Mechanism of infection control.